2012
DOI: 10.1371/journal.pone.0041523
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-7 Inhibits Epithelial-to-Mesenchymal Transition and Metastasis of Breast Cancer Cells via Targeting FAK Expression

Abstract: Focal adhesion kinase (FAK) is an important mediator of extracellular matrix integrin signaling, cell motility, cell proliferation and cell survival. Increased FAK expression is observed in a variety of solid human tumors and increased FAK expression and activity frequently correlate with metastatic disease and poor prognosis. Herein we identify miR-7 as a direct regulator of FAK expression. miR-7 expression is decreased in malignant versus normal breast tissue and its expression correlates inversely with meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
142
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(148 citation statements)
references
References 50 publications
2
142
1
Order By: Relevance
“…Similarly, miR-7 was reported to be downregulated in various cancers, including pancreatic and breast cancer, and was closely associated with the metastatic status of the patients (12,29). In the present study, we observed that the frequency of miR-7 promoter mutation was higher in the ADC type of lung cancer, although the difference was not statistically significant.…”
Section: Promoter Mutation Is Associated With Repressed Expression Ofcontrasting
confidence: 48%
See 1 more Smart Citation
“…Similarly, miR-7 was reported to be downregulated in various cancers, including pancreatic and breast cancer, and was closely associated with the metastatic status of the patients (12,29). In the present study, we observed that the frequency of miR-7 promoter mutation was higher in the ADC type of lung cancer, although the difference was not statistically significant.…”
Section: Promoter Mutation Is Associated With Repressed Expression Ofcontrasting
confidence: 48%
“…miRNA (miR)-7, a distinct member of the miRNA family, was reported to be able to regulate the biology of various tumor cells through repressing the expression of different target molecules (10)(11)(12)(13). miR-7 expression was found to be repressed in lung cancer tissues (7,14).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, ciRS‐7, the natural antisense transcript of cerebellar degeneration‐associated protein 1 (CRD1), contained approximately 70 MREs of miR‐7 24, 32, 36. Its high expression within cytoplasms could effectively lower miR‐7 activity through binding to it, thereby down‐regulating the expressions of insulin‐like growth factor‐1 receptor (IGF1R), epidermal growth factor receptor (EGFR) and focal adhesion kinase (FAK) 37, 38, 39…”
Section: Discussionmentioning
confidence: 99%
“…As miRNA plays important roles in the biological activities of living cells, increasing studies have discovered that certain aberrantly expressed miRNAs in various human cancers were involved in the oncogenesis, progression and metastasis (9). Considerable miRNAs have been characterized as oncogenes or tumor suppressors by targeting downstream genes (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%